POLA KOMUNIKASI ORGANISASI ANTARA PIMPINAN DAN KARYAWAN DI CV. KARYA ABADI MACINDO DALAM MEMBANGUN KEPUASAN KERJA - Yohanes Tommy Marsenky (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2022)
ABSTRACTGood communication patterns are essential as a means of channeling messages, ideas, ideas or thoughts, used as interaction tools to invite or influence others, and to equalize perceptions and achieve individual, group, and corporate goals. The problem in this study is, how the pattern of organizational communication between leaders and employees in building job satisfaction in CV. Karya Abadi Macindo. The research method used in this investigation is qualitative descriptive by describing the facts that occur at the research site through mandalam interview data collection and observation techniques. The results showed that there is job satisfaction with communication patterns between leaders and employees in the company built with the provision of salaries according to UMK, the provision of benefits and bonuses to employees, the attitude of leaders who are responsive to the problems faced by employees and a clean and safe work environment. Keywords: Communication Patterns, Organizational Communication, Job Satisfaction.